The Midwifery Care for Pregnant Women with Back Pain - Nurhayati (Universitas Aisyah Pringsewu, 2024)
Maternal Mortality Rate (MMR) is an indicator of the success of a country's services. Every day, approximately 830 women die from preventable causes related to pregnancy and childbirth. During pregnancy, anatomical and physiological adaptations occur in the body of pregnant women which results in various outcomes including back pain. Continuous care for pregnant, maternity, postpartum, BBL and family planning women is descriptive observational with a continuity of care approach method from the pregnancy, maternity, postpartum, newborn and family planning periods. Patients who complain of back pain get good results in the form of a decrease in the pain scale and a feeling of comfort after endorphin massage. Endorphin massage for pregnant women can help mothers feel more relaxed during their pregnancy. The birth ball makes the birth process easier under normal conditions. Oxytocin massage has a relaxing effect and helps express breast milk. Umbilical cord care is carried out to prevent infection. The choice of birth control is considered from all aspects of the patient.